2017
DOI: 10.1177/1479164117719058
|View full text |Cite
|
Sign up to set email alerts
|

High glucose–induced endothelial progenitor cell dysfunction

Abstract: Vascular complications contribute significantly to morbidity and mortality of diabetes mellitus. The primary cause of vascular complications in diabetes mellitus is hyperglycaemia, associated with endothelial dysfunction and impaired neovascularization. Circulating endothelial progenitor cells was shown to play important roles in vascular repair and promoting neovascularization. In this review, we will demonstrate the individual effect of high glucose on endothelial progenitor cells. Endothelial progenitor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 130 publications
(152 reference statements)
7
39
0
1
Order By: Relevance
“…On the other hand, although diabetes is considered one of the main target diseases for cell therapy due to the frequent ischemic events and wound healing impairments, studies regarding the effect of high glucose conditions on ECFC survival are scarce and controversial. While some studies described a direct cytotoxic effect [ 19 , 20 ], others are in full agreement with our findings showing that high glucose alone failed to induce apoptosis but inhibited ECFC angiogenic activity [ 12 , 18 , 21 ]. We also found that high glucose potentiated apoptosis triggered by TNFα, an effect that was significantly prevented by acidic preconditioning.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, although diabetes is considered one of the main target diseases for cell therapy due to the frequent ischemic events and wound healing impairments, studies regarding the effect of high glucose conditions on ECFC survival are scarce and controversial. While some studies described a direct cytotoxic effect [ 19 , 20 ], others are in full agreement with our findings showing that high glucose alone failed to induce apoptosis but inhibited ECFC angiogenic activity [ 12 , 18 , 21 ]. We also found that high glucose potentiated apoptosis triggered by TNFα, an effect that was significantly prevented by acidic preconditioning.…”
Section: Discussionsupporting
confidence: 93%
“…Although diabetes, especially the type 2 class, is one of the main target diseases for cell therapy due to its well-known healing impairments, studies regarding the effect of high glucose conditions on ECFC survival are scarce and controversial [ 12 ]. Our results revealed that high glucose alone failed to induce ECFC death (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In human umbilical vein endothelial cells (HUVECs), HG treatment was found to increase the proportion of cells showing increased levels of SA β-Gal activity [ 37 ]. Endothelial progenitor cells that were isolated from healthy subjects exposed to HG conditions or endothelial progenitor cells that were isolated from diabetic patients were also found to exhibit enhanced senescence [ 38 ]. In the present study, we have shown that A1 induces premature senescence in diabetic retinas.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that diabetes mellitus-induced hyperglycemic conditions cause vascular endothelial damage (1,2) demonstrating that hyperglycemia is associated with endothelial dysfunction and reduced blood vessel growth, with angiogenesis often compromised in patients with diabetes. Endothelial dysfunction has long been considered as the first event in the development of atherosclerosis and clinical events (3). Therefore, the maintenance of an intact endothelial layer and improvement of its functions are essential for the maintenance of healthy blood vessels and the prevention of cardiovascular complications associated with diabetes.…”
Section: Introductionmentioning
confidence: 99%